The Rise and Fall of Chloroquine/Hydroxychloroquine as Compassionate Therapy of COVID-19 - Manivannan, Elangovan; Karthikeyan, Chandrabose; Moorthy, N. S. Hari Narayana; Chaturvedi, Subash Chandra (Frontiers in Pharmacology, 2021)
The emergence and rapid spread of novel coronavirus disease (COVID-19) has posed a serious challenge to global public health in 2020. The speed of this viral spread together with high mortality rate has caused an unprecedented public health crisis. With no antivirals or vaccines available for treatment of COVID-19, the medical community is presently exploring repositioning of clinically approved drugs for COVID-19. Chloroquine (CQ) and Hydroxychloroquine (HCQ) have emerged as potential candidates for repositioning as anti-COVID-19 therapeutics and have been granted approval for compassionate use. On March 28, 2020, The US Food and Drug Administration FDA has issued emergency use authorization (EUA) for HCQ in the treatment of COVID-19. In a short period of time, on June 15, 2020, the U.S. FDA revoked the same based on its ongoing clinical trial analysis. Similarly, World Health Organization WHO began the Solidarity Trial of Chloroquine, Hydroxychloroquine, Remdesivir, Lopinavir and Ritonavir. However, on May 23, 2020, the executive body of the “Solidarity Trial” decided to put a temporary hold on HCQ trial. On June 17, 2020, WHO abruptly stopped the solidarity trial of HCQ. The current review strives to examine the basis of compassionate use of CQ and HCQ for the treatment of COVID-19 in terms of literature evidences establishing the antiviral efficacy these drugs against corona and related viruses. Furthermore, the review also critically analyses the clinical trial findings and the basis for the dynamically changing decision on the approval and withdrawal of HCQ as anti-COVID-19 therapy by US-FDA and WHO.